Students' Problem Solving Ability Based on the Fraction Concept Mastery in the PBL Model (Universitas Negeri Semarang, 2019)
This study aims to determine students' problem solving abilities based on the mastery of the concept of fractions in the PBL model. Mixed method with sequential explanatory design was used in this research. This research was conducted in class V SD Negeri 1 Cikeduk Cirebon Regency in 2018/2019. The Data obtained by tests, interviews, and observation sheets. Qualitative learning is assessed from the planning, implementation, and assessment stages. The test results of students' problem solving abilities were analyzed quantitatively by one sample t-test and classical completeness test. Students were grouped based on their concept mastery which consists of the high concept mastery category (PKT), the medium concept mastery category (PKS), and the low concept mastery category (PKR) and two subjects from each concept mastery category were chosen to be interviewed. The results showed that; (1) students' problem solving skills achieve mastery in the PBL model; (2) Increased students' concept mastery ability; (3) Students' problem solving skills in students with high concept mastery are able to master the problem solving steps of Polya-Schoenfeld theory. (4) Students' problem solving skills in students whose mastery is able to master three indicators of problem solving from four indicators; and (5) students' problem solving skills in students with low concept mastery only mastered two indicators, and the results of the final answers were not right. It can be concluded that there is an improvement of student learning outcomes in solving problems based on concepts mastery in the PBL model.